Rural-urban differences in health service utilization in upper-middle and high-income countries: a scoping review - Talis Liepins; Garry Nixon; Tim Stokes (BMC, 2024)
Abstract Purpose This scoping review aims to understand the extent and attributes of literature evaluating differences between rural and urban populations' utilization of health services in upper-middle and high-income countries. Method The review was conducted in line with established scoping review methodology guidelines. We used the "Participants, Concept and Context" framework to guide the inclusion criteria and determination of the review's scope. Studies published over a 15-year period (2008-2022) were identified using Embase, Medine, PubMed, and Scopus databases. Study attributes, areas of focus and findings were reviewed and extracted. Results The search identified 179 studies. The number of studies published looking at rural-urban differences in health service utilization has increased over time. The focus of these studies is relatively evenly split between primary and secondary sectors. The majority of studies observed less service utilization by rural populations than urban-especially so in primary-sector services. When higher rural utilization of secondary services was observed this was frequently attributed to poor access to other services that would have had the potential to mitigate the secondary demand. Studies were not commonly grounded in principles of equity or fairness and rarely offered value judgements on observed differences in utilization. There were limited system-level studies - the vast majority being disease- or service-specific analyses. We consider this a notable gap in the literature. Conclusion This scoping review identifies key parameters of studies on rural-urban variation in health service utilization. The finding that most studies observed rural populations utilized comparatively less services is concerning, in the context of general evidence about high levels of health need in rural communities. Future system-level research considering the combined variations in need and utilization appears a priority.